MASALAH SOSIAL DALAM GEGURITAN JAPATUAN: Sebuah Kajian Sosiologi Sastra (Social Problem in Geguritan Japatuan (a Traditional Balinese Poetry), a Study of Sociology of Literature) - Sukrawati, Cokorda Istri (Balai Bahasa Sumatra Barat, 2014)
This writing aims at describing the social problem occurring in one of the Balinese Traditional works entitled “Geguritan Japatuan”by sociology of literature approach. Data source was taken purposively, that is geguritan (traditional poetry) which consists of social problem. The method used in collecting data was literature review since the data was written data. Then the data was analyzed by using descriptive method that analyzed Geguritan Japatuan. Based on the analysis, the most social problem in the “Geguritan Japatuan” is the problem related with the custom, leteh and cuntaka. The infraction of the custom in term of leteh and cuntaka was finally solved by consensus. The custom in Balinese society is mostly Bali Hindu.